Problem... Solution Result... [April-July] - Hercules Incorporated (1947 Hercules Advertisements, 1947)
Advertisement for Parlon, the trade name for a chlorinated rubber product manufactured and sold by the Hercules Powder Company for use on concrete as a base coat for paint. This advertisement appeared in the April 26, 1947 issue of Business Week; the April 28, 1947 issue of Newsweek; the May 1947 issue of Nations Business; the June 2, 1947 issues of the Chicago Journal of Commerce and the Wall Street Journal; the June 4, 1947 issue of New York Journal of Commerce; and the July 1947 issue of Fortune. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Hercules Incorporated; Corporations; Advertising, Industrial; Cellulose--Chemistry; Cellulose; Ethylcellulose; Gums and resins; Rubber industry and trade